PENGARUH RASIO KEUANGAN TERHADAP TOTAL RETURN SAHAM PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA TAHUN 2010-2012 - B41108086, Nora Karlin (Jurnal KIAFE, 2015)
This research intend to find the effect of financial ratio to Total Return of Shares of the industrial corp. listed in BEI. Financial ratios used are Liquidity ratio, activity ratio, solvency ratio and market value ratio. In this research, independent variable used are Current Ratio (CR), Inventory Turnover (ITO), Debt to Equity Ratio (DER), Price Earning Ratio (PER) and dependent variable is Total Return saham. Population in this research are 38 corp. which mainly focused on F&B industry that listed in BEI for 2010-2012 and after screened in purposive sampling phase, sample reduced to 10 corp. with the data sample collected in financial report consist Current Ratio (CR), Inventory Turnover (ITO), Debt to Equity Ratio (DER), Price Earning Ratio (PER). Technique used are double linier regression and hypotheses test used t-statistic to test the coefficient of regression partially and f-statistic to test the effect of ratios simultaneously with the level of significance 5%. Partially, this research show that liquidity (Current Ratio), activity (Inventory Turnover), solvency (Debt to Equity Ratio), and market price (Price Earning Ratio) gives less-significance to Total return of Shares and simultaneously affect less-significance to Total Return of Shares. Result of this research shows that investor still can use the fundamental factor to predict the total shares return for F&B Industry in this research, only if they use different variable than used in this research. Keyword : Current Ratio (CR), Inventory Turnover (ITO), Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Total Return of Shares.